Children's subjective well-being in rural communities of South Korea and the United States. (January 2018) - Lawler, Michael J.; Choi, Changyong; Yoo, Joan; Lee, Juyeon; Roh, Soonhee; Newland, Lisa A.; Giger, Jarod T.; Sudhagoni, Ramu; Brockevelt, Barbara L.; Lee, Bong Joo
Abstract: The study examined subjective well-being of 10- to 12-year-old children from rural South Korea ( n  = 489) and rural United States ( n  = 1286) using the Children's Worlds Survey within the framework of the ecological, relationship-based model of children's subjective well-being. Applying Structural Equation Modeling to the analysis, a large proportion of the variance was explained and children's subjective well-being was predicted in both countries by microsystem factors of family relationships, parent involvement, and school quality, and individual factors of age (younger), and gender (male). Additional microsystem factors predicting subjective well-being were neighborhood quality in South Korea, and peer relationships in the United States, which may reflect contextual influences of collectivistic (South Korea) and individualistic (United States) macrosystems. Highlights: Children's subjective well-being assessed in rural South Korea and rural United States. In both countries, children tell us that families, parents, and schools matter for their well-being. South Korea children reported neighborhood quality while United States children reported peer relationships as important to their well-being. Macrosystems of collectivism in South Korea and individualism in the United States may provide context for microsystem structures affecting children's well-being.